Merajut Harmoni Parenting Wali Santri: Sinergi dengan Pondok Pesantren untuk Membangun Generasi Unggul di Jannatun Naim International Collage Lampung - Siti Patimah; Abdul Latief Arung Arafah; Deti Elice; Fahrina Yustiasari Liriwati (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
Education at Islamic boarding schools has a vital role in shaping the character and spirituality of the younger generation in Indonesia. However, the success of santri education does not only depend on educational institutions, but also on the active involvement of santri guardians through effective parenting practices. This article discusses the importance of synergy between parenting of santri guardians and Islamic boarding schools in an effort to create a superior generation based on Islamic values. With a structured parenting program and close communication between the santri guardians and the Islamic boarding school, a consistent educational environment can be created that supports children's holistic development. It is hoped that the result of this synergy will be the creation of a generation that is intelligent, has character, and is ready to face future challenges while remaining firm in the teachings of Islam.